Aqueous chemoenzymatic one-pot enantioselective synthesis of tertiary α-aryl cycloketones via Pd-catalyzed C–C formation and enzymatic CC asymmetric hydrogenation. Issue 5 (25th February 2021) - Luan, Pengqian; Liu, Yunting; Li, Yongxing; Chen, Ran; Huang, Chen; Gao, Jing; Hollmann, Frank; Jiang, Yanjun
Abstract : Aqueous chemoenzymatic two-step one-pot enantioselective synthesis of tertiary α-aryl cycloketones via Pd-catalyzed C–C formation and enzymatic CC asymmetric hydrogenation was developed. Abstract : An aqueous chemoenzymatic cascade reaction combining Pd-catalyzed C–C formation and enzymatic CC asymmetric hydrogenation (AH) was developed for enantioselective synthesis of tertiary α-aryl cycloketones in good yields and excellent enantioselectivities. The stereopreference of the enzyme in AH of α-aryl cyclohexenones was studied. An enantiocomplementary enzyme was obtained by site-directed mutation.